BO‘LAJAK BOSHLANG‘ICH SINF O‘QITUVCHILARINING KOMPETENTLIGINI OSHIRISHDA PARADIGMAL YONDASHUVNING AHAMIYATI - Hayitova, O.P. (SCIENCE and SOCIETY, 2025)
This article examines the importance of modern educational paradigms in improving the professional competence of future primary school teachers. Also, the current issues and development indicators of primary education in the Republic of Karakalpakstan, theoretical and practical aspects of the paradigm approach in improving the professional competence of future primary school teachers, its impact on the training of teachers in the pedagogical process, practical recommendations for organizing the educational process on the basis of modern pedagogical approaches such as cognitive, humanitarian and person-oriented educational paradigms in the formation of competence are developed.
Keywords: primary school; competence; educational paradigms; pedagogical approach; educational reforms; modern methodologies